2015
DOI: 10.1093/jac/dkv388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CTX-M steady-state mRNA, mRNA half-life and protein production in various STs ofEscherichia coli

Abstract: ObjectivesHigh levels of β-lactamase production can impact treatment with a β-lactam/β-lactamase inhibitor combination. Goals of this study were to: (i) compare the mRNA and protein levels of CTX-M-15- and CTX-M-14-producing Escherichia coli from 18 different STs and 10 different phylotypes; (ii) evaluate the mRNA half-lives and establish a role for chromosomal- and/or plasmid-encoded factors; and (iii) evaluate the zones of inhibition for piperacillin/tazobactam and ceftolozane/tazobactam.MethodsDisc diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Spore-forming Bacillus spp. are one of these bacteria with high levels of tolerance to harsh conditions that are currently being used in dry probiotic products due to their ability to survive in conditions of high or low temperatures, aridity, and high oxygen levels [28].…”
Section: Discussionmentioning
confidence: 99%
“…Spore-forming Bacillus spp. are one of these bacteria with high levels of tolerance to harsh conditions that are currently being used in dry probiotic products due to their ability to survive in conditions of high or low temperatures, aridity, and high oxygen levels [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from our laboratory showed that ST did not impact CTX-M protein levels, but perhaps the presence of a particular CTX-M could impact porin production. 20 The overall trend for ompC expression was highest for ST131 isolates (Figure 1) with a range of expression from 457-to 6483-fold compared with XQ13 (ST68) regardless of whether CTX-M-14 or CTX-M-15 was produced. The trend for OmpC mRNA levels in non-ST131 isolates was lower and ranged from no difference compared with XQ13 to 638-fold.…”
Section: Relative Mrna Expression and Protein Production Of Ompc And ...mentioning
confidence: 95%
“…Ten CTX-M-14-producing and 10 CTX-M-15-producing E. coli clinical isolates of various STs were collected from urine. 20 These isolates were collected from varying geographical regions to ensure that the data represented a wide distribution of CTX-M-producing isolates and not a local clonal outbreak (Table 1). The K-12 derivative WT strain BW25113 (BW) and its single-gene knockouts JW2203-1 (DompC), JW0912-1 (DompF) and JW4130-1 (Dhfq) were obtained from the Keio collection.…”
Section: Bacterial Isolates Sequencing Sequence Typing and St131 Clad...mentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted using the Ultrapure RNA Kit (Novoprotein, Shanghai, China) and reverse transcribed using the SuperRT One-Step RT-PCR Kit (Novoprotein, Beijing, China). Real time quantitative PCR (qPCR) using a SuperRT One-Step RT-PCR Kit (Novoprotein, Beijing, China) was performed and analyzed according to the protocol 57,58 .…”
Section: Analysis Of Transcriptional Intensitymentioning
confidence: 99%